Offshore Wind Farm Economic Evaluation Under Uncertainty and Market Risk Mitigation - Antonio C. Caputo; Alessandro Federici; Pacifico M. Pelagagge; Paolo Salini (Energies)
Renewable energy systems (RES) are strongly affected by many sources of uncertainty and variability. Nevertheless, traditional technical and economic evaluation methods often neglect uncertainty by deterministically assuming average nominal values, using simple sensitivity analysis to explore effects of changing conditions, or limiting to a few sources of uncertainty. Furthermore, long-term variability and changing scenarios during the life of the system are not considered. This leads to inaccurate estimation of inherent investment risk. To address this gap, this work proposes a framework for the economic evaluation of offshore wind farms, considering the effects of both epistemic and aleatory uncertainty. Uncertainty of correlations used to model the system, the variability of resources and energy prices, as well as the use of a financial hedging tool to cope with market risk, the impact of failures and disruptive events, the changing of long-term scenarios during the system’s life, and the wake effect due to wind direction variability are all considered. As demonstrated through an example of an application, this methodology will be useful to practitioners and academics to achieve a more realistic assessment of the profitability of the investment based on a more comprehensive propagation of uncertainty.